Factors associated to the occurrence of cleft lip and palate in newborns in a tertiary care Peruvian hospital. A case-control study - Plasencia-Duenas, Esteban A. (2020)
Objective: to identify factors associated to the occurrence of cleft lip and/or palate in newborns in Edgardo Rebagliati-Martins National Hospital in Lima, Peru, during the time period from November 2012 until December 2016. Materials and methods: this is an analytical observational paired case-control study, with data from the Collaborative Latin-American Study of Congenital Malformations. Sixty-one cases and sixty-one controls were analyzed. The dependent variable was the presence of cleft lip and/or palate. Clinical, epidemiological, obstetric, and prenatal variables were also analyzed. Results: cleft lip/palate with complete extension predominantly in males was the most frequent form, and it was present in 36 neonates (59%), 44 of all children in the sample (75.9%) had normal karyotype, and 40 did not have a prenatal diagnosis (65.6%). Associated malformations most frequently observed were 27 facial cases (44.2%), followed by cardiac malformations (29.6%). A statistical model using multivariate analysis was built on, and this comprised three variables: chronic disease during pregnancy (odds ratio [OR]: 3.8; 95% confidence interval [CI]: 1.11–13.8), maternal age more than 35 years (OR: 6.85; 95% CI: 2.69–17.43), and family history (OR: 14.5; 95% CI: 1.68–125.56). Conclusions: chronic diseases during pregnancy, advanced maternal age, and family history were factors that increased the frequency of cleft lip and/or palate.